ANALYSIS OF THE FIRE SEASON IN CHAPADA DOS GUIMARÃES NATIONAL PARK/MT USING GEOTECHNOLOGY DATA - Hoki, Vanusa de Souza Pacheco; Borges Pinto Junior, Osvaldo; Sanches, Luciana Sanches (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The use of geotechnologies, such as remote sensing and Geographic Information Systems (GIS), enables the monitoring of vegetation dynamics at different phenological stages associated with fire events. This study aimed to characterize the duration and spatiotemporal variability of the fire season in the Chapada dos Guimarães National Park (PNCG), from 2003 to 2023, based on an integrated analysis of the Perpendicular Moisture Index (PMI), the Normalized Difference Vegetation Index (NDVI), and Kernel density estimation. Fire hotspot data from BDQueimadas/INPE and FIRMS/NASA were used, combined with vegetation moisture maps and the spatial distribution of fire occurrences. The lowest PMI values, recorded in August and September of 2015 and 2019, indicated greater vegetation water stress compared to 2017. The NDVI for September 2017 ranged from 0.0050 to 0.229, reflecting changes in vegetation cover. A high density of fire hotspots was particularly concentrated in the buffer zone of the PNCG. The PMI proved to be effective in indicating fire susceptibility, corroborating NDVI patterns. Kernel density analysis allowed the identification of areas with the highest recurrence of forest fires, highlighting critical regions for monitoring and preventive management actions.